Complications of Adjudicating Administrative Disputes Under the Unified Judicial System in the United Arab Emirates - Ahmed Salem Alsaedi; Muhammad Najib Bin Abdullah; Mustafa 'Afifi Bin Ab. Halim (OCERINT International, 2024)
Non-Indexed Publication